Strategy-proof multi-object auction design: Ex-post revenue maximization with no wastage - Tomoya Kazumura; Debasis Mishra; Shigehiro Serizawa (Osaka University, Institute of Social and Economic Research (ISER), 2017)
A seller is selling multiple objects to a set of agents. Each agent can buy at most one object and his utility over consumption bundles (i.e., (object,transfer) pairs) need not be quasilinear. The seller considers the following desiderata for her mechanism, which she terms desirable: (1) strategy-proofness, (2) ex-post individual rationality, (3) equal treatment of equals, (4) no wastage (every object is allocated to some agent). The minimum Walrasian equilibrium price (MWEP) mechanism is desirable. We show that at each preference profile, the MWEP mechanism generates more revenue for the seller than any desirable mechanism satisfying no subsidy. Our result works for quasilinear type space, where the MWEP mechanism is the VCG mechanism, and for various non-quasilinear type spaces, some of which incorporate positive income effect of agents. We can relax no subsidy to no bankruptcy in our result for certain type spaces with positive income effect.
Keywords: D82; D44; D40; 330; multi-object auction design; strategy-proof mechanism design; ex-post revenue maximization; minimumWalrasian equilibrium price mechanism; non-quasilinear preferences; no wastage; equal treatment of equals